2009
DOI: 10.2136/sssaj2007.0245
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Metabolites as Indicators of Soil Microbial Activity and Community Composition Shifts

Abstract: The dynamics of soil microorganisms have important implications for the response of subsurface soil ecosystems to perturbations. Traditional indicators such as functional, community, activity, and carbon and nutrient pathway methods have been used to characterize soil microbial processes and ecological function; however, many of these indicators lack the ability to measure changes over large (e.g., landscape) spatiotemporal scales in soil environments. This research introduces the analysis of soil volatile org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…This N-containing aromatic compound has been previously observed to be emitted from soil (McNeal and Herbert, 2009). It is likely to originate from microbial activity as it has been reported to be an antifungal volatile emitted by Bacillus subtilis bacteria isolated from soil (Liu et al, 2008), to be released from myxobacteria during fermentation (Xu et al, 2011) and to be synthesized by an in vitro system consisting of the ectomycorrhizal fungus Tuber borchii and the Tilia americana L. plant roots (Menotta et al, 2004).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This N-containing aromatic compound has been previously observed to be emitted from soil (McNeal and Herbert, 2009). It is likely to originate from microbial activity as it has been reported to be an antifungal volatile emitted by Bacillus subtilis bacteria isolated from soil (Liu et al, 2008), to be released from myxobacteria during fermentation (Xu et al, 2011) and to be synthesized by an in vitro system consisting of the ectomycorrhizal fungus Tuber borchii and the Tilia americana L. plant roots (Menotta et al, 2004).…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that these compounds could originate from decomposition of root exudates released from living plants. Different furans are widely emitted from soils (Leff and Fierer, 2008; McNeal and Herbert, 2009), and therefore their absence in the soil mesocosm emissions was surprising. However, these compounds were also not detected in the emissions from a mountain birch forest floor with removed aboveground vegetation cover (Faubert et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Besides differences in soil-specific community composition, mVOC production in soils is strongly depending on nutrient and oxygen availability and on the physiological state of the microorganisms. The availability of nutrients and oxygen itself is again depending on several environmental factors such as soil moisture, soil texture, or microbial activity (McNeal and Herbert 2009). The availability of oxygen is a basic parameter determining the types of VOCs produced as it allows highly effective respiration.…”
Section: Effects Of Soil-related Properties On Voc Production and Relmentioning
confidence: 99%
“…In the few existing studies, the variety of VOCs measured from soils is broad, and many of these compounds are not found in aboveground plant parts. In field studies and natural soil microcosms, numerous soil-originating VOCs have been found, including alcohols, aldehydes, ketones, aromatics, carboxylic acids, esters, ethers, nitriles, sulphides, and aliphatic hydrocarbons, in addition to the most common terpenoids (Stotzky et al 1976, Janson et al 1999, Hayward et al 2001, Isidorov and Jdanova 2002, Hellén et al 2006, Asensio et al 2007a, McNeal and Herbert 2009, Greenberg et al 2012). Measurements of VOCs have traditionally been conducted mainly during growing seasons, when the VOC emissions from plants are highest.…”
Section: Current Knowledge Of Forest Floor and Soil Voc Production Anmentioning
confidence: 99%